A Study of Crack-Face Boundary Conditions for Piezoelectric Strip Cut Along Two Equal Collinear Cracks (Advances in Applied Mathematics and Mechanics, 2018)
A problem of two equal, semi-permeable, collinear cracks, situated normalto the edges of an infinitely long piezoelectric strip is considered. Piezoelectric stripbeing prescribed out-of-plane shear stress and in-plane electric-displacement. TheFourier series and integral equation methods are adopted to obtain analytical solutionof the problem. Closed-form analytic expressions are derived for various fractureparameters viz. crack-sliding displacement, crack opening potential drop, field intensityfactors and energy release rate. An numerical case study is considered for poledPZT−5H, $BaTiO_3$ and PZT−6B piezoelectric ceramics to study the effect of appliedelectro-mechanical loadings, crack-face boundary conditions as well as inter-crack distanceon fracture parameters. The obtained results are presented graphically, discussedand concluded.